Multirresistência antimicrobiana em cepas de Escherichia coli isoladas de cadelas com piometra Antimicrobial multi-resistance of Escherichia coli strains isolated from bitches with pyometra - V.M. Lara (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2008)
The antimicrobial sensibility of Escherichia coli strains isolated from the uterine content of bitches was evaluated. Fifteen E. coli strains were tested in relation to their susceptibility to different antimicrobials. The results demonstrated 100% of resistance to all tested drugs, being a quite conflicting finding compared to other works, which observed variable resistance of those bacteria to different antimicrobials but not the same multi-resistance pattern. The detection of those multi-resistance strains configures a problem, with important implications on the antimicrobial therapy. Therefore, additional investigations for a best characterization and extension of this problem are needed.